Political attitudes and elections in Lithuania - Ališauskienė, Rasa (Politologija, 2000)
During the period of 1990-2000, Baltijos tyrimai carried surveys of public opinion and analyses of socio-economic context. These surveys and analyses allow one to describe and compare several factors that exert influence on the popularity of Lithuania’s politicians. Author divides the first part of the article into three sections: politicians’ evaluations, parties, parties and politicians’ ratings. In the second part of the article presents some of the data obtained from the surveys. The data backgrounds theses as provided in the first section. Among factors which determine the popularity of the politician level of information available, the post held by the politician and his personal characteristics arc men tioned. During the last ten years, author postulates, the list of the most popular politicians, whom Lithuanian citizens might easily recognize, has undergone but little changes. The group of the most popular politicians, according to the author might be divided into two subgroups: Sąjudis activists and the politicians who joined active political life later but nevertheless receive attention of the media. It is said that Lithuania’s citizens arc better informed and thus find confidence to greater extent with regard to those politicians who hold higher posts. Last ten years have shown that politicians who arc nominated or elected to high post (Prime Minister, Minister, party leader, etc.), attract great er confidence on the part of the population in the beginning of their career, higher number of them formulate their opinion as regards those politicians. Such an increase in confidence is watched for about half a year and later decreases, as decreases the support the population entitles to the politician following his pass-away from the post. Never theless, two exceptions to the rule can be mentioned : two Presidents of the Republic of Lithuania A.Brazauskas and V.Adamkus. The level of confidence for them remained stable. In the first section author concludes that personality characteristics are an important factor determining the popularity of politician in the eyes of Lithuania’s franchise. In the second section the author provides for the premises standing behind the popularity of parties. Four complexes of factors arc believed here to be important: the party origins, the number of strong, popular leaders, image and ideology, plus, their relation to the Government. Therefore their content and relative weight is assessed. It is said that in the eyes of the population the parties maintain their image as "an inevitable evil". Two voters out of three agree that political parties, despite the fact that they arc oftentimes ineffective and do not comply with population’s needs, are necessary clement of democratic order. Author puts that during the period between elections, the Parties, which are not in the Government, attract more supporters than the governing ones. This decade, approximately 20 percent of the electorate arc said to be loyal to one party. This part of electorate kept voting for the same party both during 1992 and 1996 Seimas elections. Their values, according to the author, arc close to the imagined ideology of the party supported. When assessing upon the factors which determine the ratings of the political par ties the author comes to conclusion that these arc dependent for most on the popularity of their leaders, and not vice versa (that is, popularity of the leaders on the popularity of the parties). It is said that personification of the political process remains very strong. The majority of the franchise believes that in politics personality is more important than party, its program and/or ideology. On its part, ideology and program have strong influence on the position of the most active and best-educated part of electorate (approximately 10 percent of the total). Second part of the article presents the selected number of statistical data, which is escorted by comments. Data pertaining to the way populace evaluates the development of the country, is the direction picked positive or negative, docs the progress of democracy satisfy them or not, what is their opinion regarding the market economy and the economic situation in Lithuania, what arc the main problems the country faces is provided in tables. Besides, the interest of the population in politics, and the evolution of that interest, is presented in Part II, Section 4.5. The author gives a comparative insight into the evolution of the attitudes to different issues and phenomena and comments upon why they changed . The data is selected depending upon the age of the interviewed (18-19; 20-29, etc.) and their sex (male/female). In section 5 of the article, on the basis of the previous surveys and the results of 1997 Presidential elections and Local elections as of 2000, the author provides data concerning the intentions of the voters (the section is titled accordingly, Intentions of the Voters). Table 17 shows what party the voters, once voting for specific party, would vote for were the elections held tomorrow. Shifts with regard to the electorate of four parties - Centro Sąjjunga (Centras Party), LDDP (Labour Party), LSDP (Socialdemocrats), and the Conservatives (TS/LK) - arc depicted in that sense.